Physiological and transcriptomic analysis of the effect of overexpression of the NTPIP2;4 gene on drought tolerance in tobacco - Xu Luo; Yuanshuai Shi; Jie Tan; Tao Long; Juntao Song; Yang Liu (BMC Plant Biology)
Abstract Aquaporins are widely present in the plant kingdom and play important roles in plant response to abiotic adversity stresses such as water and temperature extremes. In this study, we investigated the regulatory role of NTPIP2;4 on drought tolerance in tobacco at physiological and transcriptional levels. In this experiment, we constructed an NtPIP2;4 overexpression vector and genetically transformed tobacco variety 'K326' to investigate the mechanism of NtPIP2;4 gene in regulating drought tolerance in tobacco at physiological and transcriptomic levels. Physiological analyses showed that overexpression plants showed low wilting under drought conditions compared to wild-type (WT), and NtPIP2;4 overexpression tobacco plants showed enhanced superoxide dismutase (SOD) and catalase (CAT) activities, lower levels of superoxide anion (O2 -), malondialdehyde (MDA), and hydrogen peroxide (H2O2) than the control, and significantly higher proline (Pro) content than the control. The leaves of NtPIP2;4 overexpressing plants and wild-type controls after drought were subjected to transcriptome sequencing, and RNA-seq analysis showed that a total of 1752 differentially expressed genes (DEGs) were obtained under drought conditions, with 1005 DEGs of up-regulated and 747 DEGs of down-regulated differentially expressed genes. The DEGs were enriched mainly in the plant MAPK signaling pathway, the plant hormone signal transduction pathway, amino sugar and nucleotide sugar metabolism, starch and sucrose metabolism and plant-pathogen interaction pathways. We also investigated the drought pathway of MAPK pathway and the auxin pathway mechanism of plant hormone signal transduction pathway, and found that the transcript levels of the genes of the relevant pathways changed, and hypothesized that NtPIP2;4 might regulate the drought resistance of plants through the expression of the relevant genes induced by auxin. This study demonstrates that overexpression of NtPIP2;4 gene can enhance the drought resistance of tobacco plants, which will provide a basis for the research on the function of tobacco NtPIP2;4 gene and the creation of new germplasm resources.